Methodology For Improving Mechanisms Of Diagnostic Correction In Primary Education - Jansaitova Jazira Bakhitjanovna (Euro Asian Journal Publishing, 2024)
This article, using a functional model for improving diagnostic correctional activities of primary school students, shows the requirements of the international assessment program and the mechanism for developing students’ reading literacy skills
Keywords: primary education; pedagogical diagnostics; correction; PISA